OP0179 Brafv600e promotes myeloid skewing in multisystemic langerhans cell histiocytosis humanized mouse model. (15th June 2017) - Biavasco, R; Norelli, M; Camisa, B; Cesana, D; Gallina, P; Gentner, B; Ponzoni, M; Dagna, L; Bondanza, A; Montini, E
Abstract : Background: Multisystemic Langerhans cell histiocytosis (mLCH) is an aggressive disease characterized by the accumulation of mononuclear phagocytes with immunohistochemical features of dendritic cell (histiocytes) 1 . Histiocytes infiltrate mostly the skin, bone marrow (BM), lung and spleen, and produce high levels of proinflammatory cyto/chemokines, leading to organ dysfunction 2, 3 . In patients, around 10% of cells in lesions carries an oncogenic mutation in the MAPK pathway, mostly BRAF V600E (70% of cases). BRAF V600E can be detected also in monocytes and BM progenitors (HSPC) from these patients, whereas only a fraction of them carries a mutation in B cells and none in T cells 4 . Objectives: To study the role of BRAF V600E in the pathogenesis of mLCH, we set up a humanized mouse model of mLCH based on the transplantation into immunodeficient mice (NSG) of human HSPC expressing BRAF V600E . Methods: We isolated HSPC from human cord blood and transduced them at two different levels (50% and 20%) with lentiviral vectors that ubiquitously express BRAF V600E, BRAF WT or GFP. Results: All BRAF V600E mice manifested severe weight loss within 7 weeks with a median of 3 and 5 weeks for 50% and 20% transduction groups, respectively. Mice showed dysplastic bone marrow (BM) with infiltration of histiocytes; lesions were present also in lungs, kidneys, CNS, spleen and liver. Immunophenotype of infiltrating histiocytes closely resembles mLCH, staining positive for CD14, CD68, S-100 and langerin. None of the control mice lost weight nor displayed organ alteration. Flow cytometry analyses of BM showed 5- to 7-fold reduction in engraftment of human cells in BRAF V600E vs GFP groups (p<0, 001). Percentage of myeloid cells increased by 3- to 4-fold in BRAF V600E vs GFP groups (p<0, 001). On the contrary, percentage of B cells was reduced by 3- to 6, 5-fold in BRAF V600E vs GFP groups (p<0, 001). Moreover, there was no difference in the percentage of GFP-positive cells between myeloid cells, whole BM and in vitro sample, suggesting a non-cell autonomous mechanism underlying this myeloid phenotype. Conclusions: In summary, we generated for the first time a human xenogeneic transplantation mouse model of mLCH, showing that BRAF V600E in human HSPC promotes myeloid skewing rather than proliferation. References: Wilejto et al. Curr Opin Rheumatol 2012. DOI: 10.1097/BOR.0b013e32834db53e. Donadieu et al. Histiocytic Disorders of Children and Adults 2005. Kannourakis et al. Br J Cancer 1994, Sep;23:S37–40. Berres et al. J Exp Med 2014, DOI: 10.1084/jem.20130977. Disclosure of Interest: None declared